T182. DIAGNOSIS INDEPENDENT SYNDROME RELATED GRAY MATTER VOLUME CHANGES IN A LARGE TRANSDIAGNOSTIC COHORT: RESULTS FROM THE FOR2107 STUDY - Stein, Frederike; Lemmer, Gunnar; Schmitt, Simon; Brosch, Katharina; Meller, Tina; Nenadic, Igor; Dannlowski, Udo; Krug, Axel; Kircher, Tilo (Schizophrenia bulletin, 2020)
BackgroundMore than a century of research on the neurobiological underpinnings of the Major Psychoses (Schizophrenia SZ, Bipolar Disorder BD, Major Depressive Disorder, Schizoaffective Disorder SZA) has been unable to identify diagnostic “markers”. An alternative approach is to study dimensional psychopathological syndromes that cut across categorical diagnoses. Brain imaging studies on the correlates of syndromes are thus far restricted to one diagnosis, however it is unclear, whether structural brain correlates of syndromes are the same across diagnoses. Previously, we have identified 7 syndromes in n=811 patients suffering from major psychoses, applying a confirmatory factor analysis, including depressed mood, negative symptoms, delusions, formal thought disorders, hallucinations, mania and increased appetite. The aim of the current study was to identify gray matter volume correlates of these syndromes across the major psychoses.MethodsWe tested the association of the above 7 psychopathological factors with whole brain GMV (voxel-based morphometry) in a sample of n=713 patients meeting DSM-IV criteria for MDD (n=550), BD (n=79), SZ (n=51) and SZA (n=33) (www.for2107.de). T1 weighted brain images were acquired at a 3-Tesla MRI. Images were pre-processed as implemented in the Cat12 (SPM12) toolbox. We performed multiple regression analyses for each factor separately and used the family wise error correction (FWE) to correct for multiple comparisons. Additionally, we tested if local VBM associations were driven by one diagnosis extracting the beta-volumes of the clusters and then comparing the subgroups using ANCOVA.ResultsThe delusion factor was negatively correlated with gray matter volume in the left inferior temporal gyrus/fusiform gyrus (k=138 voxels, x/y/z=-48/-58/-15, t=5.23, p<.05 FWE peak level) and the left amygdala/hippocampus (k=23 voxels, x/y/z=-15/-12/-12, t=4.84, p<.05 FWE peak level). The hallucinatory syndrome was negatively correlated with volume in the right thalamus proper (k=54 voxels, x/y/z=8/-4/-2, t=4.9, p<.05 FWE peak level). Extraction of the beta-volumes revealed no effect of diagnosis (delusions (F (3,708) p=.54; hallucinations (F (3,708) p=.542).DiscussionVolume changes underlying psychopathological syndromes are independent of diagnosis. We could confirm previous results from much smaller studies which have restricted themselves to single diagnoses or case control designs. Our findings open a new avenue for neurobiological research of the major psychoses, using syndrome based, dimensional approaches rather than DSM or ICD diagnoses.